LA CONVENCIÓN INTERAMERICANA SOBRE LA PROTECCIÓN DE LOS DERECHOS HUMANOS DE LAS PERSONAS MAYORES EN LA JURISPRUDENCIA DE LA SALA CONSTITUCIONAL DE COSTA RICA - Miranda Bonilla, Haideer (2021)
This research analyzes the application that the Constitutional Chamber of Costa Rica has given to the Inter-American Convention on the Protection of Human Rights of Older Persons even before its ratification by the Legislative Assembly.